A Water-Soluble Polysaccharide from the Fruit Bodies of Bulgaria inquinans (Fries) and Its Anti-Malarial Activity. (3rd May 2011) - Bi, Hongtao; Han, Han; Li, Zonghong; Ni, Weihua; Chen, Yan; Zhu, Jingjing; Gao, Tingting; Hao, Miao; Zhou, Yifa
Abstract : A water-soluble polysaccharide (BIWS-4b) was purified from the fruit bodies of Bulgaria inquinans (Fries). It is composed of mannose (27.2%), glucose (15.5%) and galactose (57.3%). Its molecular weight was estimated to be 7.4 kDa (polydispersity index, Mw/Mn: 1.35). Structural analyses indicated that BIWS-4b mainly contains (1 → 6 )-linked, (1 → 5 )-linked and (1 → 5, 6)-linked β -Gal f units; (1 → 4 )-linked and non-reducing terminal β -Glc p units; and (1 → 2 )-linked, (1 → 6 )-linked, (1 → 2, 6)-linked and non-reducing terminal α -Man p units. When examined by the 4-day method and in a prophylactic assay in mice, BIWS-4b exhibited markedly suppressive activity against malaria while enhancing the activity of artesunate. Immunological tests indicated that BIWS-4b significantly enhanced macrophage phagocytosis and splenic lymphocyte proliferation in malaria-bearing mice and normal mice. The anti-malarial activity of BIWS-4b might be intermediated by enhancing immune competence and restoring artesunate-suppressed immune function. Thus, BIWS-4b is a potential adjuvant of anti-malaria drugs.